Genomic Organization and Developmental Expression of Glutathione S-Transferase Genes of the Diamondback Moth, Plutella xylostella - Sonoda, Shoji (University of Wisconsin Library, 2006)

(untitled)
In the present study, we cloned and sequenced the entire coding regions of two glutathione S-transferase (GST) genes encoding PxGSTs and PxGSTe from the diamondback moth, Plutella xylostella L. (Lepidoptera: Yponomeutidae), along with their respective 5′ and 3′ flanking regions. The PxGSTs gene was composed of four exons and three introns. Based on amino acid identity with GST genes from other insects, this gene was classified as a member of the Sigma class. The gene encoding PxGSTe had an intron in the 5′ flanking region. Southern blot analysis showed that PxGSTs was a single copy gene, whereas there were homologous members of the PxGSTe gene in the P. xylostella genome. RNA gel blot analysis indicated that the expression levels of both genes changed with the developmental stage of P. xylostella.